Intraocular Pressure Changes After Selective Laser Trabeculoplasty (SLT) in Open-Angle Glaucoma - Amalia Mayasari; Maharani Cahyono (Majalah Oftalmologi Indonesia, 2016)
Background: Selective laser trabeculoplasty (SLT) use laser to selectively target pigmented trabecularmeshwork without producing collateral damage to adjacent non-pigmented cells or structures. A previousdata suggests that SLT is effective at every stage of open-angle glaucoma (OAG). SLT can be used asa first-line therapy, alternative to medical therapy, or as an adjunctive therapy to topical glaucomadrops. The aim of this study was to determine the changes in intraocular pressure (IOP) after SLT inpatients with OAG.Methods: Design of this research was cohort-prospective study. Twenty-six eyes of 18 patients withOAG were participated in this study. All the patients were treated with 180o SLT to the temporaltrabecular meshwork and followed by 180o SLT to the nasal trabecular meshwork 1 week after the firsttreatment. A frequency-doubled (532 nm) Q-switched Nd:YAG laser with a 400 Î¼m spot size wasused to deliver 0.4-1.0 mJ of energy for 0.3 ns to perform the procedure. Additionally, IOP in thetreated eye was assessed and measured with Goldman applanation before SLT, and 1 hour, 1 week,and 2 weeks following complete SLT. All patientes were given corticosteroid (prednisolone acetat 1%eyedrop) 4 times a day for 7 days after SLT to prevent elevation of IOP caused by inflammation.Results: The average pre-SLT IOP were 19.94 mmHg. The mean IOP 1 hour post-SLT was slightlyincrease. IOP 2 weeks after complete SLT showed a significant decrease compared to before SLT(Wilcoxon-test, before: p=0.033; 1 hour: p=0.915; 1 week: p=0.098; 2 weeks: p=0.009)Conclusion: Intraocular pressure lowering effect was significant at 2 weeks after SLT treatment. SLTeffectively reduces IOP in open-angle glaucoma. It can be used as a primary or adjunctive therapy inpatient with open-angle glaucoma.Keywords: obstructive MGD, quality of meibum, ocular surface damage